Concentration of Total petroleum Hydrocarbons and Selected Heavy Metals In Soil And plant nearby Al-Nassiriya oil Refinery South of Iraq - k.k., Noora; y. AL-khafaji, Bassim (University of Thi-Qar Journal of Science, 2019)
The present study deal with measure concentration of Total petroleum hydrocarbons (TPHs) and selected heavy metals (HMs) (Cd , Pb , Co , V, and Ni) in soil and plant phragmits austriles (cav.) nearby AL-Nassiriya oil refinery during the period extended from winter up to summer 2018 . Some environmental factors such as , pH, salinity‰ , Electrical conductivity (Ec.) and soil temperature were measured , also total organic carbon (Toc) % content in soil was determined, and soil texture was analyzed and both of them expressed as percentage . The result observed that the range of the following factors were : soil temp. ranged from (26-36) ◦c , pH (7.3-7.9) , Ec. (14.3-25.3) µs/cm and salinity (5.1-7.3)‰ , while the value of Toc ranged from (0.7-8.55)% , soil texture was silty soil in control station , but they were sandy soil at polluted stations . The mean concentration of TPHs in soil , St.1 , St.2 , St.3 and St.4 were (16.47 ,14.78 ,12.65 and 1.36) µg /gm dry weight respectively , while the mean concentration of HMs in the soil for both season were Cd (0.78 ), Pb (26.85), Co (26.83), Ni (227.17) and V (95.67) µg /gm dry weight . In plant (shoot and root) part , mean concentration of TPHs were (4.86 and 8 .44) µg /gm dry weight respectively ,whereas the mean concentration of heavy metals in both parts for both seasons were Cd (0.49 and 0.65) , Pb (30.36 and 49.25).